Nanoparticles for hyperthermic therapy: synthesis strategies and applications in glioblastoma - Verma J (Dove Medical Press, 2014)
Jyoti Verma,1,2 Sumit Lal,1 Cornelis JF Van Noorden31Department of Medicine, Harvard Medical School, 2Division of Endocrinology, Diabetes and Hypertension, Brigham and Women's Hospital, Boston, MA, USA; 3Department of Cell Biology and Histology, Academic Medical Centre, University of Amsterdam, Amsterdam, The NetherlandsAbstract: Glioblastoma multiforme (GBM) is the most common and most aggressive malignant primary brain tumor in humans. Current GBM treatment includes surgery, radiation therapy, and chemotherapy, sometimes supplemented with novel therapies. Despite recent advances, survival of GBM patients remains poor. Major challenges in GBM treatment are drug delivery across the blood–brain barrier, restriction of damage to healthy brain tissues, and limitation of resistance to therapies. This article reviews recent advances in the application of magnetic nanoparticles (MNPs), gold nanorods (GNRs), and carbon nanotubes (CNTs) for hyperthermia ablation of GBM. First, the article introduces GBM, its current treatment, and hyperthermia as a potential modality for the management of GBM. Second, it introduces MNPs, GNRs, and CNTs as inorganic agents to induce hyperthermia in GBM. Third, it discusses different methodologies for synthesis of each inorganic agent. Finally, it reviews in vitro and in vivo studies in which MNPs, GNRs, and CNTs have been applied for hyperthermia ablation and drug delivery in GBM.Keywords: hyperthermia, targeted drug delivery, SPIONs, gold nanorods, carbon nanotubes